The Role of Teacher Feedback in Developing Students’ Writing Performance - Qorina Hasanah Qorina; Muhammad Rafli Rasyid; Revi Rosalia; Febby Meriska; Subadi Dwi Maizen; Eric Alessandro Azzari (Journal of Innovative and Creativity, 2025)
Feedback is an essential element in the learning process, playing a crucial role in helping students improve their learning outcomes, including writing skills. This study aims to explore in depth the role of teacher feedback in developing students’ writing performance and the factors affecting its effectiveness. A qualitative descriptive method was employed, involving one teacher and several students from a secondary school in Bengkulu City, selected purposively. Data were collected through in-depth interviews, classroom observations, and documentation of students’ writings before and after receiving feedback. Data analysis followed the steps of data reduction, data presentation, and conclusion drawing. The findings indicate that teachers provide various types of feedback, including corrective, developmental, and motivational feedback, applied flexibly according to student needs. Feedback was found to significantly improve students’ writing quality, particularly in language accuracy, content completeness, paragraph coherence, and text organization. Improvements were especially evident after students revised their writings based on teacher feedback. Furthermore, students’ attitudes and responses to feedback strongly influenced the success of the revision process. Most students responded positively, feeling helped and more confident, although a small number initially experienced anxiety before understanding the purpose of the feedback.In conclusion, teacher feedback plays a vital role in enhancing students’ writing quality and should be applied consistently, clearly, and tailored to individual student needs. These findings are expected to serve as a reference for teachers in optimizing feedback strategies in writing instruction.